Genetic alterations of differentiated thyroid carcinoma in iodine‐rich and iodine‐deficient countries. (5th June 2016) - Vuong, Huy Gia; Kondo, Tetsuo; Oishi, Naoki; Nakazawa, Tadao; Mochizuki, Kunio; Inoue, Tomohiro; Tahara, Ippei; Kasai, Kazunari; Hirokawa, Mitsuyoshi; Tran, Thong Minh; Katoh, Ryohei
Abstract: BRAF V600E mutation, RET rearrangements, and RAS mutations are the common genetic alterations in differentiated thyroid carcinomas derived from follicular thyroid cells. However, the relationship between these alterations and iodine intake is still controversial. To clarify the influence of iodine intake on the occurrence of differentiated thyroid carcinomas, we performed molecular analyses for two differentiated carcinomas, papillary thyroid carcinomas (PTCs) and follicular thyroid carcinomas (FTCs), from an iodine‐rich country (Japan) and an iodine‐deficient country (Vietnam). We examined 120 PTCs (67 Japanese and 53 Vietnamese) and 74 FTCs (51 Japanese and 23 Vietnamese). We carried out allele‐specific polymerase chain reaction (AS‐PCR) for BRAF V600E, PCR and direct sequencing for RAS mutations (codon 12, 13, and 61 in NRAS, HRAS, and KRAS ), and RT‐PCR for RET/PTC1 and RET/PTC3 . BRAF V600E was present in 55/67 (82.1%) Japanese PTCs and 44/53 (83%) Vietnamese PTCs. RET/PTC1 was identified in only one PTC from each country, and no samples had RET/PTC3 . NRAS mutation was found in 17/51 (33.3%) Japanese FTCs and 4/23 (17.4%) Vietnamese FTCs. NRAS mutation was cited in codon 61 (20 cases) and codon 12 (one case). None of FTCs had KRAS or HRAS mutations. There were no significant differences in the prevalence of BRAF V600E, RET/PTC, or RAS mutations between the two countries. Our study showed no differences in genetic alterations of thyroid cancers from iodine‐rich and iodine‐deficient countries, possibly suggesting that iodine intake might not affect the genetic alterations of differentiated thyroid cancer. Abstract : Iodine consumed in food in the Japanese and Vietnamese populations is not associated with the genetic alterations seen in differentiated thyroid carcinomas. However, our findings contribute to the understanding of carcinogenesis of thyroid tumors.